Perceptions and use of the vacuum mattress in prehospital trauma care: a cross-sectional surve - Lorenzo Galli; Leonardo Ceccanti; Ilario Bocchi; Flavio Gheri (Scenario® - Il Nursing nella sopravvivenza, 2026)
Introduction: spinal immobilization has traditionally been considered a key component of prehospital trauma care to prevent secondary spinal cord injury. However, growing evidence has questioned the routine use of rigid immobilization such as spine board, highlighting potential complications and limited clinical benefit. In response, the concept of spinal motion restriction has been introduced, promoting more selective approaches to spinal stabilization. Despite evolving recommendations, variability in clinical practice persists, and the perceptions and decision-making processes of prehospital providers regarding immobilization devices remain poorly explored. Materials and Methods: a cross-sectional observational survey was conducted among prehospital healthcare professionals operating within the emergency medical services system of Azienda USL Toscana Centro, Italy. A structured questionnaire consisting of 15 multiple-choice items was developed to assess knowledge, perceptions, and reported practices regarding the use of spinal immobilization devices, with particular focus on the vacuum mattress. Responses were collected anonymously through an online survey platform and analyzed using descriptive statistics. Results: a total of 86 prehospital professionals participated in the survey, including nurses (22.1%) and advanced rescuers (77.9%). While the vacuum mattress was perceived by 74.4% of respondents as the most effective immobilization device, the spine board was considered the fastest device by 82.6%. Despite this perceived effectiveness, the vacuum mattress appeared to be rarely used in clinical practice, with 94.2% of participants reporting fewer than five uses per year. Conclusions: a discrepancy exists between participants' perceived effectiveness and the actual use of spinal immobilization devices in prehospital trauma care. Operational factors such as application speed, provider familiarity, and logistical considerations may influence device selection. Improving training and aligning clinical practice with evolving SMR recommendations may support more consistent and evidence-informed trauma care.